Effects of dam structures on genetic diversity of freshwater fish Sinibrama macrops in Min River, China. (October 2016) - Zhao, Liangjie; Chenoweth, Erica L.; Liu, Jun; Liu, Qigen
Abstract: In order to explore the effect of different dam structures on the genetic diversity of freshwater fish, the genetic diversity of Sinibrama macrops in Min River was investigated using mitochondrial control region (D-loop) sequences. Populations of S. macrops at Jianyang and Shaowu rivers were separated from the rest of the system by low dams and the population at Gutian was isolated from the rest of the river by a high dam. The haplotype diversity in the samples analyzed varied from 0.577 to 0.933 and nucleotide diversity varied from 0.0031 to 0.00441. The lowest values of haplotype diversity and nucleotide diversity were obtained from Gutian. Indices of genetic differentiation between populations, gene flow, analysis of molecular variance and net genetic distance between populations showed widespread gene exchange among different populations, with the exception of Gutian and Yongtai. These results may be associated with the isolation of Gutian by the high dam. The result of neutrality test and mismatch distributions showed that the evolutionary history of Gutian population was different from others in the river system. Our results imply that high dams have a larger effect on S. macrops, leading to reduction of genetic diversity and genetic differentiation from other populations. Highlights: The genetic effect of different dam structures have been evaluated. The low genetic diversity and significant differentiation existed in population separated by a high dam. The high level genetic diversity and gene flow existed in populations separated by low dams. Overall, high dam have a larger effect than low dam in genetic diversity and genetic differentiation.